Al-‘Alaqah bayn al-‘Ulamā’: Dirāsah Ta’ṣīlīyah li al-Thaqāfah al-Islāmīyah fī al-Ma’āhid al-Taqlīdīyah fī Jāwā - Wahab, Muhbib Abdul; Suwito, Suwito (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2001)
The role of kyai (religious leaders) in pesantren (Islamic Boarding School) has long been the object of study for many reaserchers. A notable example is the study of Clifford Geertz in which he obseerves the role of kyai as agents pf culture. In this study, Geertz maintains that kyai act as filters in the flow of information tp student (santri), spreading that which the kyai deem useful for the discarding that which may endanger them.DOI: 10.15408/sdi.v8i3.684